2008
DOI: 10.1007/s00702-008-0027-6
|View full text |Cite
|
Sign up to set email alerts
|

Proteasomal abnormalities in cortical Lewy body disease and the impact of proteasomal inhibition within cortical and cholinergic systems

Abstract: Dementia with Lewy bodies (DLB) accounts for 15-20% of the millions of people worldwide with dementia. In the current work we investigate the association between proteasome dysfunction and the development of cortical Lewy body pathology. Analysis of post-mortem cortical tissue indicated levels of the alpha-subunit of the 20S proteasome were significantly reduced in DLB cortex, but not Alzheimer's, in comparison to control and this reduction correlated with both the severity and duration of dementia. Applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Thus, volume change in these structures may reflect trans-synaptic neuronal loss, consistent with previous observations in lactacystin-lesioned animals [79]. However, a role for concomitant glial cell pathology cannot be excluded.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, volume change in these structures may reflect trans-synaptic neuronal loss, consistent with previous observations in lactacystin-lesioned animals [79]. However, a role for concomitant glial cell pathology cannot be excluded.…”
Section: Discussionsupporting
confidence: 88%
“…Marked cholinergic deficits accompanied by inclusions positive for aSyn and Ubi suggest that proteasomal abnormalities are present in cortical LBD [64].…”
Section: Consensus Pathologic Guidelines For the Diagnosis Of Dementimentioning
confidence: 99%
“…Additional molecular alterations converge in the pathogenesis of DLB, including impaired autophagy and ubiquitin-proteasome system of protein (4650), as well as altered responses to protein misfolding (51). Preliminary studies have shown impaired mitochondrial activity and oxidative damage involving proteins, lipids, and DNA in the neocortex in DLB (52, 53); α-synuclein is one of the targets of oxidative damage in the frontal cortex in DLB (54).…”
Section: Introductionmentioning
confidence: 99%